2018
DOI: 10.1016/j.athoracsur.2017.11.033
|View full text |Cite
|
Sign up to set email alerts
|

How to Adjust Neochordae Length Accurately in Degenerative Mitral Regurgitation

Abstract: We describe a simple technique for the accurate adjustment of polytetrafluoroethylene neochordae length in degenerative mitral regurgitation using the annuloplasty ring's own suture as a reference instead of using sophisticated or less precise maneuvers. Two threads of the annuloplasty ring suture are placed at the level of the mitral valve annulus plane to be used as a reference to tie the neochordae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…A simple method described by Kasegawa is based on readjusting chordal length by placing tourniquets and optimizing the length after competence testing 33 . Alternatively, the plane of the annuloplasty ring's suture proved to be an effective point to adjust the optimal length, even just considering the anterior annulus and a dedicated prosthetic ring has been developed accordingly 34–36 …”
Section: Surgery For Degenerative Mitral Regurgitationmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple method described by Kasegawa is based on readjusting chordal length by placing tourniquets and optimizing the length after competence testing 33 . Alternatively, the plane of the annuloplasty ring's suture proved to be an effective point to adjust the optimal length, even just considering the anterior annulus and a dedicated prosthetic ring has been developed accordingly 34–36 …”
Section: Surgery For Degenerative Mitral Regurgitationmentioning
confidence: 99%
“…33 Alternatively, the plane of the annuloplasty ring's suture proved to be an effective point to adjust the optimal length, even just considering the anterior annulus and a dedicated prosthetic ring has been developed accordingly. [34][35][36] Last but not least, a fundamental technique based on the nonresectional statement is the 'double orifice' originally described by Pomerantzeff and later identified as 'edge-toedge' which aims to reduce the valve incompetence suturing in the A2-P2 zone in order to create a double-orifice area. 37 This technique 'respects' native structures, although it does not reproduce a physiological competence (Fig.…”
Section: 'Respect'mentioning
confidence: 99%
“…Despite its success, proper sizing of neochordae remains a challenge as the procedure is performed on a flaccid heart, but its accuracy cannot be assessed until the heart is beating, and the slippery nature of ePTFE that complicates knot typing. Different techniques, tools [14][15][16][17][18][19][20][21][22][23] and algorithms 24 to determine optimal size were reported, and configurations such as pre-measured chordae are now in use 25,26 . Borger et al summarized the limitations and challenges with all of these techniques, concluding that anatomical dimensions in a fully loaded state may be the best guides 27 .…”
Section: Introductionmentioning
confidence: 99%
“…30 The artificial neochord implantation repair technique, though it is reversible, has its own challenges in length estimation, configuration optimization, and the limited ability to address redundant tissue. [31][32][33][34][35][36] A few studies also reported a large range of artificial neochord numbers, 37,38 yet limited evidence exists regarding the optimal number of artificial neochordae to be implanted for primary MR. Overall, the presence of a large variety of MV repair techniques, which vary greatly in exact deployment details, suggests an important knowledge gap in our understanding of how 1 particular repair technique is better than others.…”
mentioning
confidence: 99%